Reliance Loss, Dignity, and Marital Freedom: Legal Responsibility for Unilateral Engagement Cancellation in Indonesia and the Netherlands - Fitrothul Mubarokah; Aprodytha Widya Oryza (RechtIdee, 2026)
Study Objectives: This research analyzes the legal responsibility arising from the unilateral annulment of an engagement and compares the legal approaches in Indonesia and the Netherlands to protect women from losses incurred as a result of such unilateral cancellation.Method/Approach: The method used is normative law research with a case, conceptual, and comparative approach.Novelty: This study focuses on the judge's decision to classify engagement as a legal relationship, thereby qualifying the annulment of the engagement as an unlawful act.Findings: The results show that Indonesian courts treat the annulment of unilateral engagement as an unlawful act, deeming it contrary to social values, norms of decency, ethics, and prevailing norms. The Dutch legal system generally does not treat engagement as a binding legal relationship and emphasizes the principle of individual freedom in deciding to marry.Conclusion: The comparative results indicate that Indonesia places greater emphasis on legal protection for those who suffer harm, particularly women, while the Netherlands places greater emphasis on legal certainty and individual freedom